Persepsi Petani Terhadap Program Kartu Tani Di Desa Golo Kantar Kecamatan Borong Kabupaten Manggarai Timur - Arman Ndau, Wensislaus; Hudin, Robertus; Nini, Maklina (BiSTeK Pertanian, 2024)
One of the benefits of using a farmer card is to access subsidized fertilizers. Farmer cards are those programmed by the government and can function to ease all farmers' affairs in making loans, transactions, savings and regarding the acquisition of subsidized fertilizers. This research was motivated by problems in the farmer card program which according to the community was less useful for them, especially in terms of accessing fertilizer. The farmer card is expected to be able to overcome the problem of fertilizer distribution that is not on target and is expected to be able to provide welfare for every farmer owned by farmers with the fertilizer obtained, so that the farm that is run produces satisfactory production for the farmers themselves. The results showed that, on average, the number of farmers who did not understand the farmer card was 60%, while those who understood the farmer card were 37%. This is due to the lack of socialization from related agencies, causing a lack of understanding of farmers towards the farmer card program, especially given the fact there are some farmers who have not studied at all. This farmer card has also not been benefited by farmers, so farmers have difficulty getting subsidized fertilizer and have to spend expensive costs to obtain fertilizer.